Chapter Humanism and the Renaissance in Recent Histories of Ukrainian Literature - Siedina, Giovanna (Biblioteca di Studi Slavistici, 2020)
In this article, the author analyzes how the broad theme of the reception of Humanism and Renaissance is treated in two important histories of Ukrainian literature, respectively Muza Roksolans'ka. Ukrajins'ka literatura XVI-XVIII stolit' by Valerij Ševčuk (Kyiv, "Lybid'", 2004-2005), in two volumes, and Istorija ukrajins'koji literatury in twelve volumes (2014-) published by the publishing house of the Academy of Sciences of Ukraine Naukova Dumka. The disappearance of Soviet ideological constraints has brought about the emergence of various aspects of this theme: the multilingualism (especially as regards literature written in Latin), the multiple identity of writers of the so-called Pohranyččja, the literature written in Latin, are just a few. However, some aspects still need to be addressed: among then the supranational approach should be adequately considered when dealing with the spread of Humanism-Renaissance.